2019
DOI: 10.1111/joa.13014
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular alterations of muscularis propria in the human anterior vaginal wall in pelvic organ prolapse

Abstract: In the pathophysiology and progression of pelvic organ prolapse (POP), it has been demonstrated that there is a reorganisation of the muscularis propria of the anterior vaginal wall due to a phenotypic smooth muscle cell to myofibroblast switch. An abnormal deposition of collagen type III seems to be influenced by the involvement of advanced glycation end‐products. The aim of the present study was to evaluate the hypothesis that this connective tissue remodelling could also be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The enrichment of the term ECM organization and disassembly in most cell types suggested that diverse types of vaginal cells are widely involved in ECM dysregulation. In particular, the terms collagen catabolic process and collagen fibril organization were enriched in upregulated genes in smooth muscle cells from POP samples, while muscle system process was enriched in downregulated genes, implying that the phenotypic function of smooth muscle cells might switch and play a vital role in collagen metabolism when prolapse occurs, consistent with previous studies reporting that smooth muscle cells undergo an aberrant switch from a contractile to a synthetic ECM phenotype and contribute to the distensibility and fragility of the prolapsed vaginal wall 33 . Another notable finding was the enrichment of immune reaction disorders in DEGs in multiple cell types from POP samples.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The enrichment of the term ECM organization and disassembly in most cell types suggested that diverse types of vaginal cells are widely involved in ECM dysregulation. In particular, the terms collagen catabolic process and collagen fibril organization were enriched in upregulated genes in smooth muscle cells from POP samples, while muscle system process was enriched in downregulated genes, implying that the phenotypic function of smooth muscle cells might switch and play a vital role in collagen metabolism when prolapse occurs, consistent with previous studies reporting that smooth muscle cells undergo an aberrant switch from a contractile to a synthetic ECM phenotype and contribute to the distensibility and fragility of the prolapsed vaginal wall 33 . Another notable finding was the enrichment of immune reaction disorders in DEGs in multiple cell types from POP samples.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, tissue remodeling-related interactions such as the TGFB1–TGFBR2 interaction were gained between smooth muscle cells and some cell types, indicating that these cells participate in ECM and tissue modeling. The phenotypic switch from smooth muscle cells to myofibroblasts could be the underlying cause of structural changes in the muscularis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…MFs were also considered to be transited from smooth muscle cells according to phenotypic characteristics and structural changes in the muscularis (Sferra et al, 2019). Cells in Bs2 coexpressed smooth muscle cells and myofibroblasts, as previously suggested by their expression of MYH11, ACTG2, and DES of smooth muscle cells and TAGLN and ACTA2 of myofibroblasts.…”
Section: Diversity Of Basal/stromal Cellsmentioning
confidence: 92%
“…However, the pathophysiology of POP is still unclear and is likely multifactorial [9]. POP is associated with the weakening of connective tissue and muscles in the pelvis and with neuromuscular dysfunction [10,11]. Insufficient collagen amount and changes in the extracellular matrix (ECM) of the pelvic floor are molecular changes that lead to the development of POP [12].…”
Section: Introductionmentioning
confidence: 99%